Overcoming Hurdles in Science Practicum: Exploring Challenges and Solutions for Fifth Grade Students : Mengatasi Kendala Praktikum Sains: Menggali Tantangan dan Solusi Bagi Siswa Kelas V - Darmayanti, NWS; Janawati , Desak Putu Anom; Sudirman, I Nyoman; Lismayanti, Ni Luh; Persi, Ni Nengah (Pedagogia : Jurnal Pendidikan, 2023)
The purpose of this study is to describe the obstacles to the implementation of science practicum for grade V elementary school students.This study uses a qualitative approach with a descriptive method. The population in this study were ten students. The sampling technique used is saturated sampling, that is, all members of the population are sampled. The sample, all fifth grade students and fifth grade teachers were used. The number of questionnaires used were 10 statements given to students and 10 questions were given to the fifth grade teacher for interviews. The interview data were described by summarizing the results, while the questionnaire analysis used descriptive analysis techniques with percentage calculations. From interviews with teachers, it was found that the implementation of the experiment in fifth grade was still lacking because it was rare to carry out the experiment and there were many obstacles in terms of tools and materials as well as the practical guide. The results of the student questionnaire, 40% of students stated that the implementation of the experiment went quite well, while 60% of the students stated that the implementation of the experiment was not going well, in the sense that the implementation of the experiment was rarely carried out by the teacher. The obstacles to implementing practicum are mainly the lack of tools and materials for practicum, the absence of a special place practicum, not having special guidance for practicum and the lack of teacher readiness in teaching practicum because there is no special practicum guide.